2013
DOI: 10.1111/hepr.12264
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of percutaneous radiofrequency ablation and hepatic resection for small, poorly differentiated hepatocellular carcinomas

Abstract: As hepatic resection has greater efficacy than RFA in the treatment of poorly differentiated HCC, even in cases with a small tumor size, we recommend its use for this malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 26 publications
(58 reference statements)
1
23
0
Order By: Relevance
“…In addition, there were no recognizable local recurrences that could be clearly attributed to the residual tumor at the treatment site. All the patients in this study were treated with hepatic resection, and if they had been treated with local ablation therapy, the prognosis for pathological vascular invasion positive patients might have been poorer than those reported for negative patients . Several previous studies have reported the negative impact of pathological vascular invasion in HCC patients treated with surgical resection .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, there were no recognizable local recurrences that could be clearly attributed to the residual tumor at the treatment site. All the patients in this study were treated with hepatic resection, and if they had been treated with local ablation therapy, the prognosis for pathological vascular invasion positive patients might have been poorer than those reported for negative patients . Several previous studies have reported the negative impact of pathological vascular invasion in HCC patients treated with surgical resection .…”
Section: Discussionmentioning
confidence: 81%
“…Poorly differentiated HCC is reported to be correlated with microvascular invasion or satellite lesions, even though it is quite difficult to regard pathological tumor differentiation as a routine preoperative task. Besides, the outcome for small but poorly differentiated HCC treated with ablation therapy is reportedly much worse than for patients undergoing hepatic resection . We previously reported that the preoperatively‐evaluable contrast‐to‐noise ratio T 2 ‐weighted MRI was a predictive factor for poor differentiation .…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study from Japan compared RFA with RXN in patients with small, poorly differentiated tumors: the maximum tumor size was 2 cm in the RFA group and 2.5 cm in the RXN group. RFA for these small tumors was found to be significantly inferior, demonstrating a cumulative 5‐year survival rate of 32.7%, whereas RXN yielded a survival rate of 67.5%; the recurrence‐free survival rate also was found to be significantly lower in the RFA group . Furthermore, a Japanese nationwide survey of 12,968 patients with tumors measuring <3 cm found significantly lower odds of death and disease recurrence in patients who underwent RXN compared with those who underwent RFA .…”
Section: Discussionmentioning
confidence: 98%
“…Outcomes were analyzed for patients with tumors measuring ≤20 mm, 21 to 30 mm, 31 to 50 mm, or 31 to 35 mm. The 20‐mm cutoff value was chosen on the basis of studies demonstrating longer survival and lower disease recurrence with RXN compared with RFA in patients with early‐stage HCC measuring <20 mm . The 30‐mm cutoff value was derived from published reports (including the current American Hepato‐Pancreato‐Biliary Association consensus statement) recommending RFA for tumors measuring <30 mm .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation